Retrospective study of efficacy of adjuvant chemotherapy using tegafur-uracil in patients with non-small cell lung cancer with primary tumor size of 4.1–5.0 cm - Adachi, Hiroyuki; Nishii, Teppei; Yamamoto, Taketsugu; Nagashima, Takuya; Ishikawa, Yoshihiro; Ando, Kohei; Woo, Tekkan; Maehara, Takamitsu; Nakayama, Haruhiko; Masuda, Munetaka (Journal of Thoracic Disease, 2019)
Background: The staging of patients with a tumor of diameter 4.1–5.0 cm and no lymphatic/distant metastases have been up-graded to stage IIA in the latest 8th edition of the TNM staging system. However, the efficacy of adjuvant tegafur-uracil (UFT) therapy in these patients, which has been recommended in the guideline issued by The Japan Lung Cancer Society, remains unclear. We evaluated the efficacy of adjuvant UFT therapy among a cohort by retrospective analyses of multicentric database. Methods: In 2005–2007, 130 patients with p-stage IB non-small cell lung cancer (NSCLC) (diagnosed according to the 7th edition of the TNM staging system) and tumor size of ≥3.1 cm underwent anatomic complete resection at nine of our affiliated hospitals. We retrospectively reviewed the clinicopathological characteristics and the outcomes among these patients. Results: Ninety-eight patients had tumor size of 3.1–4.0 cm (T2a group), whereas 32 patients had tumor size >4.0 cm (T2b group). Overall, patients who received adjuvant UFT showed a tendency of better outcomes than patients who did not [hazard ratio (HR) 0.564; 95% confidence interval (CI), 0.257–1.238, P=0.147]. In subgroup analyses, patients who received adjuvant UFT also tended to show better outcomes than those who did not in both T2a group and T2b group (HR 0.504; 95% CI, 0.202–1.255, P=0.132 in T2a group and HR 0.855; 95% CI, 0.181–4.033, P=0.843 in T2b group, respectively). Conclusions: Our results suggest that adjuvant UFT therapy have the potential to improve postoperative outcomes even in patients with p-stage IIA disease, as classified according to the 8th edition of the TNM staging system.